2022
DOI: 10.7731/kifse.203e195d
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Scaling Law of Fire Phenomena in Compartment with Horizontal Natural Opening using Numerical Simulation

Abstract: The scaling law was examined using numerical simulation for fire phenomena in a compartment with a horizontal natural opening in this study. The results of the large-scale conversion of the scaled model numerical simulation results ([Small-scale] condition) from the earlier studies obtained by applying the scaling law were compared to those of the large-scale numerical simulation performed in this study ([Large-scale] condition). The overall trends for the effects of horizontal natural opening area and fire so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 12 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…This aids in understanding and predicting the compartment fire phenomena and in designing buildings to reduce human and property damage.On the other hand, research on compartments with ceiling vents is applicable in atriums, theater, and ships [1]. Some studies on fire phenomena in compartments with ceiling vents have been reported [1][2][3][4][5]. Zhang et al[1] conducted a numerical simulation on the effects of ceiling vent location (center and corner) on smoke filling process, oxygen concentration, gas temperature, and vent flow characteristics (pressure, velocity, and mass flow rate) in a compartment fire with a natural ceiling vent.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This aids in understanding and predicting the compartment fire phenomena and in designing buildings to reduce human and property damage.On the other hand, research on compartments with ceiling vents is applicable in atriums, theater, and ships [1]. Some studies on fire phenomena in compartments with ceiling vents have been reported [1][2][3][4][5]. Zhang et al[1] conducted a numerical simulation on the effects of ceiling vent location (center and corner) on smoke filling process, oxygen concentration, gas temperature, and vent flow characteristics (pressure, velocity, and mass flow rate) in a compartment fire with a natural ceiling vent.…”
mentioning
confidence: 99%
“…On the other hand, research on compartments with ceiling vents is applicable in atriums, theater, and ships [1]. Some studies on fire phenomena in compartments with ceiling vents have been reported [1][2][3][4][5]. Zhang et al…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, according to the horizontal vent area and fire location in case of a stage fire in a real-scale theater, the mass flow rate of horizontal vent flow was evaluated using the mass flow rate result of vent flow obtained from numerical simulation of the reduced-scale model and the scaling law. Park et al [10] investigated the scaling law for fire phenomena by performing numerical simulations for enclosure fires in which a horizontal vent existed. The accuracy of the scaling law for the mass flow rate and velocity distribution of the horizontal vent flow and the temperature distribution in the enclosure was checked based on the results of the reduced-scale model and full-scale numerical simulation.…”
mentioning
confidence: 99%
“…They reported that the fire size had a significant effect on the average gas temperature rise when compared to the horizontal vent area. However, in these studies [3,[9][10][11][12], a single horizontal vent was used in a fire situation and the research under the condition of two horizontal vents is insufficient. When there are two horizontal vents, the vent flow behavior and fire phenomena can be affected by the condition of the two horizontal vents.…”
mentioning
confidence: 99%